Role of Language in India’s Cultural Diplomacy - Dr. Mukesh Kumar Srivastava (Universitas Muhammadiyah Sidoarjo, 2022)
Linguistic antiquity and diversity of this country have been major attractions for the peopleacross the world and language has been an integral part of cultural diplomacy. Almost everycountry strives towards teaching their own language to foreigners and disseminate andpropagate their own culture. India, as the land of one of the most ancient languages andlargest number of languages and dialects, has appealed to foreign people with long lastingconsequences. The fact that many western scholars studied Sanskrit to delve deeper intoIndian culture is a testimony to such attraction. Realising this fact, Indian government hasprioritized teaching Indian languages to propagate Indian culture in the international arenaand has endeavoured to promote language as part of its cultural diplomacy. In this context,the paper is an effort to unfold to what extent language is important to India’s culturaldiplomacy and how language as a resource is utilized to promote Indian culture abroad.